2019
DOI: 10.1080/14686996.2019.1627174
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated liposomes: immunological responses

Abstract: A commonly held view is that nanocarriers conjugated to polyethylene glycol (PEG) are nonimmunogenic. However, many studies have reported that unexpected immune responses have occurred against PEG-conjugated nanocarriers. One unanticipated response is the rapid clearance of PEGylated nanocarriers upon repeat administration, called the accelerated blood clearance (ABC) phenomenon. ABC involves the production of antibodies toward nanocarrier components, including PEG, which reduces the safety and effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
322
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(325 citation statements)
references
References 121 publications
(167 reference statements)
0
322
0
3
Order By: Relevance
“…A well-recognized approach able to prolong the plasmatic half-life of a colloidal system is based on the coating of its surface by means of hydrophilic derivatives (as in the case of PEG) with the aim of decreasing its identification and elimination [27]. However, the multiple administration of PEG-coated systems determines the appearance of an accelerated blood clearance (the so-called ABC phenomenon) [28,29]. For this reason, the PLGA nanoparticles proposed in our work were developed by using the poloxamer 188 as a stabilizer because it can confer long circulating properties to the particles, avoiding the use of PEG [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A well-recognized approach able to prolong the plasmatic half-life of a colloidal system is based on the coating of its surface by means of hydrophilic derivatives (as in the case of PEG) with the aim of decreasing its identification and elimination [27]. However, the multiple administration of PEG-coated systems determines the appearance of an accelerated blood clearance (the so-called ABC phenomenon) [28,29]. For this reason, the PLGA nanoparticles proposed in our work were developed by using the poloxamer 188 as a stabilizer because it can confer long circulating properties to the particles, avoiding the use of PEG [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in the last decades, the PEGylation process has become a standard in drug/nanocarrier functionalization for the development of advanced drug delivery systems [172,173]. However, a number of investigations has reported unexpected adverse immune responses such as the rapid clearance of PEGylated nanocarriers upon repeat administration, a phenomenon called accelerated blood clearance (ABC) [174]. In fact, the patients who undergo a treatment with PEGylated nanocarriers may stimulate the formation of antibodies that recognize (and bind) to PEG (i.e., anti-PEG antibodies) [174].…”
Section: Lipidsmentioning
confidence: 99%
“…However, a number of investigations has reported unexpected adverse immune responses such as the rapid clearance of PEGylated nanocarriers upon repeat administration, a phenomenon called accelerated blood clearance (ABC) [174]. In fact, the patients who undergo a treatment with PEGylated nanocarriers may stimulate the formation of antibodies that recognize (and bind) to PEG (i.e., anti-PEG antibodies) [174]. Therefore, patients that acquire anti-PEG antibodies exhibit an accelerated blood clearance and a lower drug efficacy [174,175].…”
Section: Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility for improving stability is the aptamers PEG conjugation. Furthermore, it has been shown that PEG formulation reduces immune responses in vivo [41]. The thermal stability of siRNA is another parameter to be considered in gene silencing activity when it is conjugated to aptamers [38].…”
Section: Aptamer In the Delivery Of Therapeutic Nanoparticles Containmentioning
confidence: 99%